Experimental Study on the Effect of Gas Pressure on Ultrasonic Velocity and Anisotropy of Anthracite - Bo Wang; Jialin Hao; Shengdong Liu; Fubao Zhou; Zhendong Zhang; Heng Zhang; Huachao Sun (Geofluids)
To research the elasticity of gas-bearing coal fluid-solid two-phase medium with seismic exploration method is critical to the prevention of gas disasters. To investigate the elasticity, the ultrasonic elastic test of anthracite samples under different gas pressures was carried out and the ultrasonic velocity and anisotropy of the samples were analyzed in this study. The results show that the velocities (P- and S-waves) decrease in turn in the strike, dip, and vertical directions. However, a negative linear correlation is proved to exist between ultrasonic velocity and gas pressure. With the increase of gas pressure, the anisotropy degree of both the P-wave and the S-wave of the samples decreases but the declining degree of the P-wave is greater than that of the S-wave. In addition, the decrease in velocity and the anisotropy degree of the P-wave is greater than that of the S-wave, indicating that the P-wave is more sensitive to gas pressure changes in terms of velocity and its anisotropy degree.